Evaluation of Holistic Learning and Independent Curriculum: Enhancing Education Quality Through Religious Moderation - Enung Nugraha; Encep Syarifudin (Research Synergy Foundation, 2026)
Issues in implementing the Independent Curriculum or Kurikulum Merdeka, and in integrating religious moderation, often hinder holistic evaluation of learning, thereby affecting educational quality in Islamic higher education. This study examines the influence of holistic learning evaluation on the implementation of the Kurikulum Merdeka and its impact on educational quality, with a focus on religious moderation at UIN SMH Banten. Using a quantitative explanatory approach, data were collected from 174 PGMI students via validated questionnaires (CFA loadings >= 0.60, CR >= 0.70, AVE >= 0.50; Cronbach's alpha > 0.80). Holistic learning evaluation is a comprehensive assessment of cognitive, affective, and psychomotor domains. At the same time, religious moderation refers to balanced, tolerant, and inclusive Islamic values measured by indicators of fairness, respect, and anti-extremism. Data were analysed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with AMOS. The results show that learning evaluation significantly affects educational quality (beta = 0.482, p < 0.001) and the Kurikulum Merdeka (beta = 0.396, p < 0.01), while the Kurikulum Merdeka also significantly improves educational quality (beta = 0.531, p < 0.001). Religious moderation has no significant direct effect on educational quality (beta = 0.082, p > 0.05) and does not moderate the effect of the Kurikulum Merdeka (p > 0.05). Model fit is acceptable (CFI = 0.907, RMSEA = 0.050, CMIN/DF = 1.434). The findings imply that PTKIN should strengthen learning evaluation and curriculum implementation systems to enhance educational quality, while religious moderation should be integrated through curriculum design and academic culture rather than as a direct influencing factor.